MANAJEMEN PEMBELAJARAN DALAM MENGEMBANGKAN HASIL BELAJAR ANAK USIA DINI DI KELOMPOK BELAJARAZ-ZAIDAN KEDAUNG KOTA TANGERANG SELATAN - Adrian Romansah; Hendrayadi Hendrayadi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to describe learning management in developing early childhood learning outcomes at the Az-Zaidan Learning Group in Kedaung, South Tangerang City. This study uses a qualitative descriptive approach with a field research type. The research subjects included the head of the institution and teachers, while data were collected through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions, while data validity was tested using triangulation. The results of the study indicate that learning management at the Az-Zaidan Learning Group has been implemented through the stages of planning, implementation, evaluation, and follow-up in a fairly systematic manner. In the planning stage, teachers organize learning activities by adjusting the theme, objectives, methods, media, and children's developmental needs. In the implementation stage, learning takes place interactively, fun, and child-centered through a play-while-learning approach and the use of concrete media. In the evaluation stage, teachers conduct continuous assessments through observation, progress notes, and documentation of children's activities. This learning management has been proven to contribute to the development of children's learning outcomes in the cognitive, language, motor, social-emotional, religious and moral values, and independence aspects.